55.5k views
3 votes
2a²-2ab-3b²+9 when a=3 and b=2​

User IqqmuT
by
5.1k points

2 Answers

0 votes

Answer:

3

Explanation:

2(3)^2 - 2(3)(2) - 3(2)^2 + 9

2(9) - 12 - 3(4) + 9

18 - 12 - 12 + 9

= 3

Answer from Gauth math

User Clever Neologism
by
5.2k points
4 votes
  • a=3,b=2


\\ \sf\longmapsto 2a^2-2ab-3b^2-9


\\ \sf\longmapsto 2(3)^2-2(3)(2)-3(2)^2-9


\\ \sf\longmapsto 2(9)-12-3(4)-9


\\ \sf\longmapsto 18-12-12-9


\\ \sf\longmapsto 6-18


\\ \sf\longmapsto -12

User Justin Khoo
by
5.4k points